Leadership and Compensation as Predictors of Employee Morale and Job Satisfaction as Interveners in the Asadana Semesta Cooperative, Denpasar Branch - Made Mulyadi; Luh Gede Elvina Adi Saputri; Nyoman Rasmen Adi; I Wayan Meryawan (Enrichment : Journal of Management, 2022)
This study aims to determine and analyze the influence of leadership, compensation, and job satisfaction on employee morale. Data were collected from 125 respondents using the Google Form format questionnaire technique. Then the data were analyzed using SEM-PLS version 3 inferential statistical analysis. From the results of the research analysis it was found that: (1) Leadership and compensation had a significant positive effect on job satisfaction with p values of 0.000 and 0.000 respectively, less than 0.05. (2) Leadership, compensation and job satisfaction have a significant positive effect on work morale with p values of 0.037 each; 0.036 and 0.001 are smaller than 0.05. (3) Job satisfaction is a partial mediation on the influence of leadership and compensation on morale.